Effects of flavonoids on fatty acid accumulation and its molecular mechanisms in oilseed rape - YAN Tao; XUAN Lijie; JIANG Lixi (浙江大学学报. 农业与生命科学版)
Oilseed rape (Brassica napus L.) is one of the most important oil crops worldwide, and has a large planting area in Yangtze River basin. As one of the four major edible oils, rapeseed oil plays a fundamental role in human life activities. In addition, with the increasing global demand for rapeseed oil, raising oilseed rape production becomes an important direction of rapeseed breeding. As one of the most widely distributed secondary metabolites in nature, flavonoids play a critical part in plant growth and development. Flavonoids can not only improve stress tolerance, but also regulate various physiological activities of plants. However, the role of flavonoids in determining seed oil contents and the evolutionary mechanism of how pigments accumulate in seed coats remain elusive. In this review, we highlighted the metabolism, distribution, and function of flavonoids and its inhibiting effects on fatty acid accumulation in rapeseed. Understanding the molecular mechanism of flavonoids affecting fatty acid accumulation can provide a theoretical basis for increasing oil content of seeds by regulating the allocation of carbon sources in the future.